(untitled) (Nativa, 2025)
The impact of rare-earth elements (REEs) on living organisms is still unexplored. This study aimed to determine the toxicological properties of lanthanum (La) under prolonged exposure to the benthic amphipod Hyalella azteca, Saussure. The artificially created environmental condition models were water with La spiking in concentrations ranging from 0.16 to 160 µmol L-1 (mass concentrations of 0.0006 - 0.6 mg L-1) as La₂(SO₄)₃·8H₂O. The observation period lasted 40 days. Based on mortality rates, La concentrations of 160 and 16 µmol L-1 (22.4 and 2.24 mg L-1) were toxic in the acute experiment. In contrast, concentrations of 1.6, 0.8, and 0.16 µmol L-1 (0.224, 0.112, 0.022 mg L-1) exerted delayed chronic toxic effects on H. azteca. The linear dimensions and body mass of the amphipods increased in response to La concentrations of 0.16 and 0.8 µmol L-1, but further increases of metal concentrations reduced the parameters compared to lower concentrations. In all test groups except 0.16 µmol L-1, a significant increase in food consumption (biomass of Acer platanoides L.) was observed compared to the control. This effect is attributed to the compensation of toxic stress through increased feeding activity. H. azteca exhibits adverse effects of La exposure. Mortality and morphological parameters serve as the most sensitive test endpoints for these amphipods. Keywords: bioassay; survival; feeding behavior; chronic toxicity. Toxicidade do lantânio para anfípodes Hyalella azteca com exposição prolongada RESUMO: Muitas questões sobre os efeitos dos elementos de terras raras sobre organismos vivos ainda não foram estudadas. O objetivo deste trabalho foi determinar as propriedades toxicológicas do lantânio em exposição prolongada aos anfípodes bentônicos Hyalella azteca Saussure. Os meios-modelo foram água com aditivo La na faixa de concentração de 0,16 - 160 µmol L-1 (concentrações em massa de 0,0006 - 0,6 mg L-1) na forma de La2(SO4)3·8H2O. A duração das observações foi de 40 dias. Em termos de mortalidade, as concentrações de La de 160 e 16 µmol L-1 (22,4 e 2,24 mg L-1) foram tóxicas no experimento agudo, e as concentrações de La de 1,6, 0,8 e 0,16 µmol L-1 (0,224, 0,112 e 0,022 mg L-1) tiveram efeito tóxico crônico tardio na H. azteca. O tamanho linear e o peso dos crustáceos aumentaram em resposta às concentrações de La de 0,16 e 0,8 µmol L-1, o que elevou ainda mais a concentração do metal em comparação com concentrações mais baixas. Em todas as variantes, exceto 0,16 µmol L-1, houve um aumento significativo no consumo de alimentos (biomassa de Acer platanoides L.) em comparação com o controle, devido à compensação do estresse tóxico pela nutrição. Assim, o H. azteca experimenta os efeitos negativos do La. A morte e os parâmetros morfológicos são as funções de teste mais sensíveis em esses crustáceos. Palavras-chave: bioensaio; sobrevivência; comportamento alimentar; toxicidade crónica.